Investigating travel servicescapes : drivers, motivators, and outcomes of airport travellers' evaluations - Yerimou, Pantelitsa (My University, 2025)
The current thesis explores environmental factors in airports that influence travellers' emotions, satisfaction and airport image. It delineates how cultural elements and travellers’ responsiveness contribute to airport satisfaction and image evaluations. Addressing the identified gaps that include a) a predominant focus on airports’ functional aspects, b) a vague examination of emotions and c) lack of insights pertaining to the effects of sense of place and environmental responsiveness, the thesis conducts two studies. Study 1, uses sequential mixed-methods consisting of a survey with 534 international travellers, and a focus group with 4 senior managers of an international airport, in order to examine how sense of place stimuli contribute to travellers' airport image. Study 2, uses a concurrent mixed-methods approach comprised by a survey with 376 international travellers and 22 interviews, the study examined the integration of human and physical-related factors, along with sense of place stimuli and responsiveness as moderators of the environment-satisfaction nexus. Findings reveal that environmental stimuli (i.e., ambiance and layout) make a significant contribution on travellers’ emotions, airport image, and satisfaction. In both phases, sense of place revealed significant moderating effects, with environmental responsiveness also marking significant results. Based on these insights, new research areas are addressed and recommendations for improving traveller experiences are offered to practitioners and policymakers. Discussions on authenticity are expanded and guidelines are provided on the construct’s future measurements and strategic utilisation for effective airports environment planning.
Keywords: Airport Environment; Servicescape; Emotions; Image; Satisfaction; Sense of place